Famatinian inner arc: Petrographical observations and geochronological constraints on pegmatites and leucogranites of the Comechingones pegmatitic field (Sierras de Córdoba, Argentina) - Demartis, Manuel (2017)
The Comechingones pegmatitic field comprises granitic pegmatites and leucogranites hosted by mylonitic rocks from the Guacha Corral shear zone. Pegmatites consist of variably sized, internally zoned bodies, with late replacement units. Leucogranites are fine-grained rocks that form small bodies with tabular-to lens-like shapes. Field relationships and petrographic observations suggest a synkinematic emplacement of both rock types with respect to the main deformational event of this shear zone. U-Pb LA-ICP-MS analyses on zircon crystals indicate crystallization ages of 473.8 ± 3.9 and 474.8 ± 12.2 Ma for the granitic pegmatites and leucogranites, respectively, suggesting that they originated coevally at around 474 Ma. This age provides a first-order time constraint on the deformation of the Guacha Corral shear zone. Using ages and pressure estimations, along with an average pressure gradient of 1GPa/35 km for the continental crust, an exhumation rate of approximately 0.1 mm/a and 10.5 km of total amount of exhumation were calculated for the time span between the early Ordovician and the late Devonian in this part of the Sierras Pampeanas. The inherited ages obtained in zircon crystals from the leucogranites display a distribution pattern that strongly resembles those of the metasedimentary rocks of the Pampean metamorphic belt, suggesting that equivalents of these rocks should have been involved in the melting processes that originated the leucogranites.